The Welfare State in Kazakhstan: Development Based on International Experience and International Standards - RAKHIMOVA, Gakku N.; KUSSAINOV, Sergazy; ZHANGUTTIN, Baurzhan O.; SIMTIKOV, Zhomart K.; BURIBAYEV, Yermek A.; KHAMZINA, Zhanna A. (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the article lies in the need to modernize the social protection system of Kazakhstan to solve the problems of poverty. The study aims to offer opportunities for the transformation and implementation of international experience in the field of social security in the legislation of Kazakhstan. Applying the legal comparative method, the authors identified the main parameters of the social protection systems of the European member states of the International Labor Organization and the Organization for Economic Co-operation and Development. Analysis of the development of legislation on social security and social insurance has revealed the possibility of transforming the legislation of Kazakhstan in accordance with foreign standards and suggest steps to be taken to build a welfare state: systematization and codification of legislation on social security and social insurance; the continuation of the formation of the legal framework for compulsory social insurance for temporary disability, for pregnancy and childbirth; updating health insurance legislation; legislative consolidation of specific criteria and standards that will allow more clearly determine the types and volumes of guaranteed social security.